Certification of Safety-Critical Systems: Seeking new approaches toward ensuring the safety of software-intensive systems. - Leveson, Nancy G.; Thomas, John P. (Communications of the ACM, 2023)
This article provides a current state of certification of safety-critical systems. The article begins with discussing limitations to current certification approaches, unsuccessful previous attempts to modernize certification, and potential areas of improvement in the development of these software-intensive systems and the certification of them. Areas of improvement include an emphasis on safety and incorporation of human factors into both system and software engineering and new hazard analysis methods.